Implementasi Registrasi Online Seleksi Penerimaan Karyawan Baru Pada PT Lion Parcel - Dwi Rosmawati; Dedi Martono; Afrida Nurhayati (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
The use of technology in a current system can speed up the work process, including in the new employee recruitment system. This research is intended to describe the new employee recruitment system and evaluate the new employee recruitment process implemented by PT Lion Express (Lion Parcel). The method applied in data collection is by interviewing and seeing firsthand the process of recruiting new employees at PT Lion Express (Lion Parcel). In accordance with the results of research that has been done by the author, it can be concluded that the employee recruitment process carried out by the personnel department already has a systematic stage. In the recruitment process there are still several problems that hamper as long as the process can be an evaluation of the company for the future. Obstacles encountered include the process of registering prospective employees for the implementation of psychological tests which are considered ineffective because they are still based on emails received and announcements of applicant data completeness are still done one-by-one by e-mail to applicants, thus consuming the work of HR department personnel. Therefore, a web-based Smart system is needed that can facilitate registration and announcement of lack of data completeness online. So that companies can maximize the process of hiring new employees, it is recommended that the selection of new employees use a system that can accommodate the obstacles that often occur in the process of hiring new employees. The system design uses UML diagrams and PHP programming languages.